Cytocompatibility of stabilized black phosphorus nanosheets tailored by directly conjugated polymeric micelles for human breast cancer therapy - M. Biedulska (Nature Portfolio, 2021)
Abstract The novel procedure of few-layer black phosphorus (FLBP) stabilization and functionalisation was here proposed. The cationic polymer PLL and non-ionic PEG have been involved into encapsulation of FLBP to allow sufficient time for further nanofabrication process and overcome environmental degradation. Two different spacer chemistry was designed to bind polymers to tumor-homing peptides. The efficiency of functionalisation was examined by RP-HPLC, microscopic (TEM and SEM) and spectroscopic (FT-IR and Raman) techniques as well supported by ab-initio modelling. The cell and dose dependent cytotoxicity of FLBP and its bioconjugates was evaluated against HB2, MCF-7 and MDA-MB-231 cell lines. Functionalisation allowed not only for improvement of environmental stability, but also enhances therapeutic effect by abolished the cytotoxicity of FLBP against HB2 cell line. Moreover, modification of FLBP with PLL caused increase of selectivity against highly aggressive breast cancer cell lines. Results indicate the future prospect application of black phosphorus nanosheets as nanocarrier, considering its unique features synergistically with conjugated polymeric micelles.